Social And Economic Life Of Uzbek Ssr (1925-1940) (Zien Journal of Social Sciences and Humanities, 2024)
In the article has been analyzed social and economic life of Uzbek SSR in 1925-1949 by the helping scientific literature and main sources and periodicals. Besides, in 1930–1932 alone, 638,131 collective farms were created in the republic through administrative oppression, open violence, economic pressure methods, and political repression, and the collectivization plan opened in the research as well.